Guidance and Supervision of Regional Innovation Post-Implementation of PP 38 The Year 2017 Regarding Regional Innovation - Lily Latul (International Journal of Regional Innovation, 2021)
Rapid global developments make people demand real improvements from the government so that the impact can be felt directly, such as increasing competitiveness, improving public welfare, and empowering communities. The government responded to this push by issuing several regulations that are expected to accelerate service change in Indonesia. One of them is by issuing Government Regulation No. 38 of 2017 concerning Regional Innovation which is used as a solid foothold in guarding the transformation of governance at the local level. The purpose of this study is to provide an idea of ​​guidance and supervision that the Ministry of Home Affairs must carry out, in this case, is APIP.